K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

8 tháng 9 2017

(2x-1)^2=1/4

x=3/4

8 tháng 9 2017

cảm ơn

PT \(\Rightarrow2x^2+2x-3x-6=2x^2-x+4x-8-2\)

\(\Rightarrow-4x=-4\) \(\Leftrightarrow x=1\)

Vậy \(x=1\)

Ta có: \(2x\left(x+1\right)-3\left(x+2\right)=x\left(2x-1\right)+4\left(x-2\right)-2\)

\(\Leftrightarrow2x^2+2x-3x-6=2x^2-x+4x-8-2\)

\(\Leftrightarrow2x^2-x-6=2x^2+3x-10\)

\(\Leftrightarrow2x^2-x-6-2x^2-3x+10=0\)

\(\Leftrightarrow-4x+4=0\)

\(\Leftrightarrow-4x=-4\)

hay x=1

Vậy: x=1

 

2 tháng 2 2023

a) \(\dfrac{x}{3}=\dfrac{4}{12}\Rightarrow x=\dfrac{4}{12}\cdot3=\dfrac{12}{12}=1\)

b) \(\dfrac{x-1}{x-2}=\dfrac{3}{5}\) (Điều kiện : \(x\ne2\))

\(\Rightarrow5\left(x-1\right)=3\left(x-2\right)\)

\(\Leftrightarrow5x-5=3x-6\Leftrightarrow5x-3x=-6+5\Leftrightarrow2x=-1\Leftrightarrow x=-\dfrac{1}{2}\)

c) \(2x:6=\dfrac{1}{4}\Leftrightarrow2x=\dfrac{1}{4}\cdot6=\dfrac{6}{4}=\dfrac{3}{2}\Leftrightarrow x=\dfrac{3}{2}:2=\dfrac{3}{2}\cdot\dfrac{1}{2}=\dfrac{3}{4}\)

d) \(\dfrac{x^2+x}{2x^2+1}=\dfrac{1}{2}\)

\(\Rightarrow2\left(x^2+x\right)=2x^2+1\)

\(\Leftrightarrow2x^2+2x=2x^2+1\)

\(\Leftrightarrow2x^2+2x-2x^2=1\Leftrightarrow2x=1\Leftrightarrow x=\dfrac{1}{2}\).

25 tháng 10 2015

(x+2)(x^2-2x+4)-x(x-1)(x+1)+2x=2

<=> x3 - 2x2 + 4x + 2x2 - 4x + 8 - x(x2 - 1) + 2x = 2

<=> x3 + 8 - x3 + x + 2x = 2

<=> 3x + 8 = 2

<=> x = -2

24 tháng 12 2019

1) =>2x+4+4+x=11

     =>2x+4+4+x-11=0

      =>3x-3=0

       =>3x=3

       => x=1

 Vậy x  thuộc {1}

2)=>x+x+1+2x+4=3

    =>x+x+1+2x+4-3=0

   =>4x+2=0

   =>4x=-2

   =>x=-2/4

   =>x=-1/2

Vậy x thuộc {-1/2}

23 tháng 9 2021

\(a,\Leftrightarrow x^3-8-x\left(x^2-9\right)=1\\ \Leftrightarrow x^3-8-x^3+9x=1\\ \Leftrightarrow9x=9\Leftrightarrow x=1\\ b,\Leftrightarrow8x^3+12x^2+6x+1-8x^3 +12x^2-6x+1-24x^2+24x-1=0\Leftrightarrow1=0\Leftrightarrow x\in\varnothing\)

23 tháng 9 2021

a) \(\Leftrightarrow x^3-8-x^3+9x=1\)

\(\Leftrightarrow9x=9\Leftrightarrow x=1\)

b) \(\Leftrightarrow8x^3+12x^2+6x+1-8x^3+12x^2-6x+1-24x^2+24x-6=5\)

\(\Leftrightarrow24x=9\Leftrightarrow x=\dfrac{3}{8}\)

8 tháng 7 2017

1/2x+x-2=-3/4

(1/2+1)x=-3/4+2

   3/2x=5/4

       x=(5/4)/(3/2)

       x=5/6

         

20 tháng 9 2017

a, 3x-(2x+1)\(=2\)

\(\Leftrightarrow3x-2x-1=2\)

\(\Leftrightarrow3x-2x=2+1\)

\(\Leftrightarrow x=3\)

3 tháng 10 2017

a) \(3x-\left(2x+1\right)=2\)

\(3x-2x-1=2\)

\(x-1=2\)

\(x=3\)

vay \(x=3\)